2011
DOI: 10.2337/dc11-0476
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Renin-Angiotensin Blockade on Retinopathy in Type 1 Diabetes Vary With Glycemic Control

Abstract: OBJECTIVEOptimal glycemic control slows diabetic retinopathy (DR) development and progression and is the standard of care for type 1 diabetes. However, these glycemic goals are difficult to achieve and sustain in clinical practice. The Renin Angiotensin System Study (RASS) showed that renin-angiotensin system (RAS) blockade can slow DR progression. In the current study, we evaluate whether glycemic control influenced the benefit of RAS blockade on DR progression in type 1 diabetic patients.RESEARCH DESIGN AND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…DR is one of the most common microvascular complication of diabetes mellitus 111 . Many factors are involved in the pathogenesis of DR such as metabolic disorders like hyperglycemia, high blood pressure, hyperlipidemia, age, and oxidative stress 59, 112.…”
Section: Resultsmentioning
confidence: 99%
“…DR is one of the most common microvascular complication of diabetes mellitus 111 . Many factors are involved in the pathogenesis of DR such as metabolic disorders like hyperglycemia, high blood pressure, hyperlipidemia, age, and oxidative stress 59, 112.…”
Section: Resultsmentioning
confidence: 99%
“…Up-or downregulation of RA system activity does not have to result from alterations in mRNA levels only; the level of protein and activity in the RA system should also be examined. However, inhibitors of the RA system are effective against diabetic retinopathy (13)(14)(15)(16)(17). RA system inhibitors can act through inhibition of ligand production or inhibition of receptor action.…”
Section: Discussionmentioning
confidence: 99%
“…The Diabetic Retinopathy Candesartan Trials (DIRECT) [14,15], using the ARB candesartan in type 1 and 2 diabetes, showed a clear trend towards less severe retinopathy with RAS blockade. A smaller trial, the Renin-Angiotensin System Study (RASS), reported that RAS blockade with both the ARB losartan and the angiotensin-converting enzyme (ACE) inhibitor, enalapril, resulted in reduced retinopathy progression in type 1 diabetes [16]. Experimental evidence concerning the effect of ARBs is sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the reninangiotensin system (RAS), mainly by its major effector peptide angiotensin-II and its receptor, angiotensin-II receptor 1 (AT1), has been shown to play an important role in the pathophysiology of diabetic nephropathy, neuropathy and retinopathy [12,13]. Evidence comes mainly from clinical intervention studies [14][15][16]; RAS inhibition partly and selectively ameliorated diabetes-induced changes [16] or reduced the incidence of diabetic retinopathy in patients [15]. The underlying mechanisms, however, have not been systematically explored.…”
Section: Introductionmentioning
confidence: 99%